Effects of dietary supplementation of arginine-silicate-inositol complex on absorption and metabolism of calcium of laying hens - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Hayirli, Armagan; Komorowski, James R.; Şahin, Nurhan (Public Library Science, 2018)
The effects of supplementation of arginine-silicate-inositol complex (ASI; 49.5-8.2-25 g/kg, respectively) to laying hens were investigated with respect to eggshell quality, calcium (Ca) balance, and expression of duodenal proteins related to Ca metabolism (calbindin and tight junction proteins). A total of 360 laying hens, 25 weeks old, were divided into 3 groups consisting of 6 replicate of cages, 20 birds per cage. The groups were fed a basal diet and the basal diet supplemented with 500 or 1000 mg ASI complex per kilogram for 90 days. Data were analyzed by ANCOVA using data during the first week of the adaptation period as covariates. As the ASI complex supplementation level increased, there were increases in feed intake (P < 0.0001), egg production (P < 0.001), egg weight (P < 0.0001) and eggshell weight (P < 0.001) weight, and shell thickness (P < 0.001) and decreases in feed conversion ratio and cracked egg percentage (P < 0.0001 for both). Concentrations of serum osteocalcin (P < 0.0001), vitamin D (P < 0.0001), calcium (P < 0.001), phosphorus (P < 0.001), and alkaline phosphatase (P < 0.008) as well as amounts of calcium retention (P < 0.0001) and eggshell calcium deposition (P < 0.001), and Ca balance (P < 0.0001) increased, whereas amount of calcium excretion (P<0.001) decreased linearly in a dose-dependent manner. The ASI complex supplementation increased expressions of calcium transporters (calbindin-D28k, N sodium-calcium exchanger, plasma membrane calcium ATPase, and vitamin D receptor) and tight junction proteins (zonula occludens-1 and occludin) in the duodenum in a linear fashion (P < 0.0001 for all). In conclusion, provision of dietary ASI complex to laying hens during the peak laying period improved eggshell quality through improving calcium utilization as reflected by upregulation of genes related to the calcium metabolism. Further studies are needed to elucidate the contribution of each of the ASI complex ingredients.
Keywords: Improve Eggshell Quality; Vitamin-D; Gene-Expression; Bone Loss; Quail; Rats; Deficiency; Exchanger; Membrane; Protein